2010
DOI: 10.1371/journal.pgen.1000887
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Rat Model of Neurodegeneration Caused by Mutation in the TDP Gene

Abstract: TDP-43 proteinopathies have been observed in a wide range of neurodegenerative diseases. Mutations in the gene encoding TDP-43 (i.e., TDP) have been identified in amyotrophic lateral sclerosis (ALS) and in frontotemporal lobe degeneration associated with motor neuron disease. To study the consequences of TDP mutation in an intact system, we created transgenic rats expressing normal human TDP or a mutant form of human TDP with a M337V substitution. Overexpression of mutant, but not normal, TDP caused widespread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
186
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(203 citation statements)
references
References 56 publications
15
186
2
Order By: Relevance
“…In addition, although premature sudden death prevented the assessment of cognitive function in previous studies using mutant TDP-43 transgenic animal models, cortical neuron degeneration has been consistently observed. 11,14,19,20,28 Therefore, our findings in hemizygous TDP-43 M337V mice do not necessarily contradict previous findings only reporting motor dysfunction in TDP-43 transgenic mice. Unlike other transgenic animal models showing increased expression of total TDP-43, the hemizygous TDP-43 M337V model does not demonstrate significantly changed expression of total TDP-43 in the brain and spinal cord, 29 indicating very low transgene expression.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, although premature sudden death prevented the assessment of cognitive function in previous studies using mutant TDP-43 transgenic animal models, cortical neuron degeneration has been consistently observed. 11,14,19,20,28 Therefore, our findings in hemizygous TDP-43 M337V mice do not necessarily contradict previous findings only reporting motor dysfunction in TDP-43 transgenic mice. Unlike other transgenic animal models showing increased expression of total TDP-43, the hemizygous TDP-43 M337V model does not demonstrate significantly changed expression of total TDP-43 in the brain and spinal cord, 29 indicating very low transgene expression.…”
Section: Discussionsupporting
confidence: 63%
“…TDP-43 autoregulates its own RNA level (11,23) at least in part by stimulating excision of an intron in its 3′ untranslated region, thereby making the spliced RNA a substrate for nonsense-mediated RNA degradation (11). Furthermore, transgenic rodent models have been used to demonstrate that overriding the autoregulatory mechanism by overexpression of unregulated wild-type (24)(25)(26)(27)(28) or disease-linked mutant (26,(28)(29)(30)(31)(32)(33)(34)(35) TDP-43 transgenes can produce neurodegeneration in mice.…”
mentioning
confidence: 99%
“…However, direct evidence that these TDP-43 aggregates cause neurodegeneration has not yet been established. Some models show little or no TDP-43 aggregation, yet neurodegeneration still occurs (23)(24)(25). Other studies have shown no connection between TDP-43 aggregation and degenerative phenotypes (26,27).…”
mentioning
confidence: 99%